Comparative Outcome of Laser Hemorrhoidoplasty Versus Conventional Hemorrhoidectomy for Grade II/III Hemorrhoids - Hasan, Muhammad Hasnat Ul; Ahmed, Khalil; Khanum, Hamail; Arslan, Muhammad; Din, Qaim; Javed, Muhammad Asad (Biological and Clinical Sciences Research Journal, 2025)
Hemorrhoids are a prevalent anorectal condition with significant morbidity when symptomatic. Conventional hemorrhoidectomy remains the gold standard for grade II/III hemorrhoids but is associated with notable postoperative discomfort and extended hospital stays. Laser hemorrhoidoplasty (LHP) has emerged as a minimally invasive alternative with potentially better outcomes, though limited evidence exists in the local Pakistani population. Objective: To compare mean operative time, postoperative pain, and hospital stay between laser hemorrhoidoplasty and conventional Milligan-Morgan hemorrhoidectomy in patients with grade II/III hemorrhoids. Methods: This randomized controlled trial was conducted at the Department of General Surgery, Gulab Devi Hospital, Lahore, from January to March 2025. A total of 100 patients with symptomatic grade II/III hemorrhoids were enrolled using non-probability consecutive sampling and randomized equally into two groups: Group A underwent conventional open hemorrhoidectomy, and Group B received laser hemorrhoidoplasty. Key outcomes measured included operative time (in minutes), pain at one week post-operatively (VAS score), and hospital stay (in hours). Data were analyzed using SPSS version 26.0, and independent t-tests were applied with p < 0.05 considered statistically significant. Results: The mean age of the study participants was 42.6 ± 11.3 years. Male patients constituted 62% of the sample. The LHP group had significantly reduced mean operative time (14.8 ± 3.2 min vs. 30.2 ± 4.1 min, p < 0.001), lower postoperative pain scores (3.7 ± 0.7 vs. 6.5 ± 0.6, p < 0.001), and shorter hospital stays (8.1 ± 2.0 hrs vs. 36.4 ± 6.3 hrs, p < 0.001) compared to the conventional group. These differences remained significant across stratified analyses for hemorrhoid grade, comorbidities, and lifestyle factors. Conclusion: Laser hemorrhoidoplasty is superior to conventional hemorrhoidectomy in terms of operative efficiency, reduced postoperative pain, and shorter hospitalization. These findings advocate for the adoption of LHP as a first-line surgical intervention for grade II/III hemorrhoids in the Pakistani healthcare setting.